Emotion and Perception: The Role of Affective Information - Zadra, Jonathan R. (2011)
Visual perception and emotion are traditionally considered separate domains of study. In this article, however, we review research showing them to be less separable that usually assumed. In fact, emotions routinely affect how and what we see. Fear, for example, can affect low-level visual processes, sad moods can alter susceptibility to visual illusions, and goal-directed desires can change the apparent size of goal-relevant objects. In addition, the layout of the physical environment, including the apparent steepness of a hill and the distance to the ground from a balcony can both be affected by emotional states. We propose that emotions provide embodied information about the costs and benefits of anticipated action, information that can be used automatically and immediately, circumventing the need for cogitating on the possible consequences of potential actions. Emotions thus provide a strong motivating influence on how the environment is perceived.